Sindicalismo e associativismo docente universit??rio na Am??rica Latina - hist??ria e embates pol??ticos na contemporaneidade (1990-2010) - Paiva, Lu??s Roberto Beserra de (2016)
Higher education is , in most countries , responsible for the basic education teacher training , so the changes processed in the first are directly reflected on the whole education system to pass on the training of teachers. In education , in particular , working conditions equivalent to the teaching conditions , so in this work we understand the various levels of education as integrated and co-dependent with each other.In the late twentieth century, Latin American governments have taken the neoliberal ideology that drastically changed role of the state and public policy. Call neoliberal proposals for higher education, especially public universities, as contrarreforma since undermine the principles that guided the University Reform of C??rdoba (1918) - university autonomy, university government shared by the community, gratuitousness, the public character, hiring teachers through competition - and thus causing damage to freedom of thought and knowledge production. Worsening conditions of teaching and research, which in many circumstances coincide with the working conditions, was accompanied by measures to intensified exploitation and control of the teaching activity (proliferation of precarious work, high productivity, loss of rights). Interviewed twenty-five (25) professors from four countries (Argentina, Brazil, Colombia and Mexico), to report their perceptions of the processes that guided the implementation of the university contrarreforma and resistance of their professional category. We use also the material produced by dozens of unions and parassindicais we visited, as well as universities, government agencies, the World Bank, local media and literature production researchers on the university teacher unionism in each country. Systematize a description of these various tables and prepared a comparative analysis identifying common elements and distinct trajectories of university teachers union entities.